Altered Carbon: Reinterpreting Poe in the Age of Artificial Intelligence - Valente, Telma Elita Juliano (Farol, 2026)
This is an analysis of the first season of the science fiction series Altered Carbon, focusing on the character Poe, an AI manager at the Raven Hotel. It aims to examine the similarities between this character and the writer Edgar Allan Poe—particularly regarding his suspense and horror stories, while considering the symbiosis between author and work—alongside other literary and aesthetic references. Additionally, the study highlights the concept of transhumanism through discussions on the series’ central theme: digital immortality. To this end, the concept of intersemiotic translation is applied—defined as translation occurring across different languages ​​or sign systems, involving the interpretation of verbal signs via non-verbal means or the transfer from one sign system to another (Jakobson, 1969). The study concludes that the intersemiotic translation of Poe’s work demonstrates the enduring nature of his legacy.